Road to World Tourism Day 2022: Membangun Kesadaran Pariwisata Berkelanjutan melalui Edukasi Partisipatif di Kampung Sauwandarek, Raja Ampat - shidqi, Khairu Farras Shidqi; Hermawan, Hary (Jurnal Abdimas Pariwisata, 2025)
Road to World Tourism Day 2022: Fostering Sustainable Tourism Awareness through Participatory Education in Sauwandarek Village, Raja Ampat. This community service activity aims to foster awareness of tourism and strengthen the values of Sapta Pesona among the residents of Kampung Wisata Sauwandarek, Meos Mansar District, Raja Ampat Regency. Conducted as part of the "Road to World Tourism Day 2022" campaign, this initiative involved stakeholders from local government, the tourism office, and higher education institutions. The program included awareness-raising sessions, community discussions, and the distribution of educational materials, all aimed at promoting active community participation in sustainable tourism development. The results showed an increase in local understanding of the importance of hospitality, cleanliness, security, and environmental preservation as key components of a tourism village. This program is expected to serve as a model for other tourism villages in strengthening their human resources and preparing for more inclusive and sustainable tourism growth.